Konflik Sosial dan Budaya dalam Novel “Sekeping Cinta Untuk Yola” Karya Abas sebagai Bahan Ajar Sastra di Sekolah Menengah Atas - Ika Herliana (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2022)
This study aims to describe the novel “Sekeping Cinta Untuk Yola” written by Abas including: (1) social conflict; (2) cultural conflict; (3) implication to the learning process in Senior High School. The method implemented in the study is qualitative-descriptive with the literature sociology approach by Rene Wallek & Austin Warren (Sujarwa, 2019:40). The results of the study show that there are social conflict, cultural conflict, and implications to the learning process in Senior High School. First, there are 5 social conflicts discovered in the novel which are 5 related to affection, 5 related to responsibility, and 5 related to life’s harmony. Second, cultural conflict discovered in the novel which are 6 (15%) economy conflict, 5 (12%) local custom conflict, 10 (24%) religious conflict, 5 (12%) social status conflict, 2 (5%) cultural conflict, 4 (10%) sciences conflict, and 9 (22%) arts conflict. The conflicts attached to the novel “Sekeping Cinta Untuk Yola” written by Abas dominated by religious conflict with 24% and cultural conflict as the lowest with 5%. Third, implementations of learning materials including language aspect, psychological aspect, and cultural values. The novel is able to enhance student’s knowledge in Indonesian vocabulary, to comprehend the student’s capability which fits with its psychological development, and to represent the cultural values of society. In conclusion, this study perceives that novel “Sekeping Cinta Untuk Yola” written by Abas has the compatibility to be included in Indonesia literature learning materials for Senior High school.Keywords: social and cultural conflicts, novel, literature learning materials, Senior High School.